Răspuns :
100-[36+6×9-(a:3+15)]:3=76
[36+54-(a:3+15)]:3=100-76
[90-(a:3+15)]:3=24
90-(a:3+15)=24×3
90-(a:3+15)=72
a:3+15=90-72
a:3+15=18
a:3=18-15
a:3=3
a=3×3
a=9
[36+54-(a:3+15)]:3=100-76
[90-(a:3+15)]:3=24
90-(a:3+15)=24×3
90-(a:3+15)=72
a:3+15=90-72
a:3+15=18
a:3=18-15
a:3=3
a=3×3
a=9
100-[36+6×9-(a:3+15)]:3=76
100-[36+54-(a:3+15)]:3=76
-[36+54-(a:3+15)]:3=76-100
-[36+54-(a:3+15)]:3=-24 |×(-1)
[36+54-(a:3+15)]:3=24
36+54-(a:3+15)=24×3
36+54-(a:3+15)=72
-(a:3+15)=72-36-54
-(a:3+15)=36-54
-(a:3+15)=-18 |×(1)
a:3+15=18
a:3=18-15
a:3=3
a=3×3
a=9
100-[36+54-(a:3+15)]:3=76
-[36+54-(a:3+15)]:3=76-100
-[36+54-(a:3+15)]:3=-24 |×(-1)
[36+54-(a:3+15)]:3=24
36+54-(a:3+15)=24×3
36+54-(a:3+15)=72
-(a:3+15)=72-36-54
-(a:3+15)=36-54
-(a:3+15)=-18 |×(1)
a:3+15=18
a:3=18-15
a:3=3
a=3×3
a=9